2016
DOI: 10.2147/ott.s122653
|View full text |Cite|
|
Sign up to set email alerts
|

Isoorientin induces apoptosis, decreases invasiveness, and downregulates VEGF secretion by activating AMPK signaling in pancreatic cancer cells

Abstract: Isoorientin (or homoorientin) is a flavone, which is a chemical flavonoid-like compound, and a 6-C-glucoside of luteolin. Isoorientin has been demonstrated to have anti-cancer activities against various tumors, but its effects on pancreatic cancer (PC) have not been studied in detail. In this study, we aim to investigate whether isoorientin has potential anti-PC effects and its underlying mechanism. In PC, isoorientin strongly inhibited the survival of the cells, induced cell apoptosis, and decreased its malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 58 publications
0
11
1
Order By: Relevance
“…In recent years, intensive studies have demonstrated the protective effects of natural products against APAP-induced hepatotoxicity due to their multiple mechanisms of action in inflammation, oxidant/antioxidant balance and damage responses ( Ko et al, 2017 ; Lv et al, 2018 ). Iso (or homoorientin) is a chemical flavonoid-like compound that has been shown to exert anti-inflammatory effects and exhibit antioxidant potential ( Ye et al, 2016 ). To our knowledge, no report has investigated the protective activity of Iso against APAP-induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, intensive studies have demonstrated the protective effects of natural products against APAP-induced hepatotoxicity due to their multiple mechanisms of action in inflammation, oxidant/antioxidant balance and damage responses ( Ko et al, 2017 ; Lv et al, 2018 ). Iso (or homoorientin) is a chemical flavonoid-like compound that has been shown to exert anti-inflammatory effects and exhibit antioxidant potential ( Ye et al, 2016 ). To our knowledge, no report has investigated the protective activity of Iso against APAP-induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, AMPK, a sensor of cellular energy status, regulates cell survival and death in the presence of oxidative stress ( Shirwany and Zou, 2014 ). Iso has been reported to activate AMPK in pancreatic cancer cells ( Ye et al, 2016 ). In our study, Iso treatment significantly increased the phosphorylation of AMPK, AKT, and GSK-3β, which might contribute to Nrf2 activation and hepatoprotective effects in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized, however, that this compound did not show significant hepatotoxicity against the PLP2 cell line up to the maximal tested concentration (GI 50 > 400 μg/mL). The antiproliferative properties of luteolin-6-C-glucoside (2) have been previously reported (Conforti et al, 2009;Gundogdu et al, 2018;Huang et al, 2018;Lin et al, 2016;Pacifico et al, 2010;Shoeb et al, 2007;Ye et al, 2016;Yuan et al, 2012Yuan et al, , 2013Yuan et al, , 2014.…”
Section: Evaluation Of Cytotoxicity Of the Compoundsmentioning
confidence: 94%
“…The flavone isoorientin demonstrated antitumor activity in an in vitro model of pancreatic cancer cells, inducing apoptosis of transformed cells. The mechanism of action was established and demonstrated upregulation of Adenosin Monophosphate-activated protein kinase, an intracellular sensor that, once activated, stimulates the apoptosis of the neoplastic cells [41]. Many drugs, with a specific anti-cancer activity or no, stimulate this pathway, causing apoptosis in tumors [42,43].…”
Section: Actives Compounds Identified In the Genusmentioning
confidence: 99%